Silencing DACH1 promotes esophageal cancer growth by inhibiting TGF-β signaling. - Liang Wu (Public Library of Science (PLoS), 2014)
Human Dachshund homologue 1 (DACH1) is a major component of the Retinal Determination Gene Network. Loss of DACH1 expression was found in breast, prostate, lung, endometrial, colorectal and hepatocellular carcinoma. To explore the expression, regulation and function of DACH1 in human esophageal cancer, 11 esophageal cancer cell lines, 10 cases of normal esophageal mucosa, 51 cases of different grades of dysplasia and 104 cases of primary esophageal squamous cancer were employed. Methylation specific PCR, immunohistochemistry, western blot, flow cytometry, small interfering RNAs, colony formation techniques and xenograft mice model were used. We found that DACH1 expression was regulated by promoter region hypermethylation in esophageal cancer cell lines. 18.8% (6 of 32) of grade 1, 42.1% (8 of 19) of grade 2 and grade 3 dysplasia (ED2,3), and 61.5% (64 of 104) of esophageal cancer were methylated, but no methylation was found in 10 cases of normal esophageal mucosa. The methylation was increased in progression tendency during esophageal carcinogenesis (P<0.01). DACH1 methylation was associated with poor differentiation (P<0.05) and late tumor stage (P<0.05). Restoration of DACH1 expression inhibited cell growth and activated TGF-β signaling in KYSE150 and KYSE510 cells. DACH1 suppressed human esophageal cancer cell tumor growth in xenograft mice. In conclusion, DACH1 is frequently methylated in human esophageal cancer and methylation of DACH1 is involved in the early stage of esophageal carcinogenesis. DACH1 expression is regulated by promoter region hypermethylation. DACH1 suppresses esophageal cancer growth by activating TGF-β signaling.